Destination‐to‐origin differences and settlement intentions of Chinese internal migrants: A birth cohort analysis - Wang, Jiejing; Zhang, Yanji (Population space and place, 2022)
Research on Chinese internal migrants has gradually shifted from a focus on the rapid expansion of this population to its relationship with the restructuring of spatial distribution in cities. The settlement intentions of migrants are key to how China's urbanisation and the urban system will evolve. Yet, although there is a considerable body of research on this subject, the determinants of migrants' settlement intentions remain debatable. In this study, in light of the dramatic economic and social transition undergone by China in the past 70 years, we demonstrate the importance of considering the cohort perspective in relation to Chinese migrants' settlement intentions. Specifically, we examine the effects of differences between migrants' origins and their destinations on settlement intentions in relation to year of birth. Our results show that destination‐to‐origin differences in terms of population size, administrative level, economic condition, and public services are positively associated with migrants’ settlement intentions, whereas geographic distance and cultural distance between origin and destination are negatively related to the intention to settle in destination cities. Further, these effects vary significantly across birth cohorts. Our findings demonstrate the importance of going beyond the standard dichotomy between old and new generation that is often used in the analysis of migration trends. To achieve more inclusive urbanisation in the future, targeted policies that take into account inter‐city and inter‐cohort variations are critical to addressing obstacles to the settlement of migrants in destination cities.